The Pathogenic Aspects of Human Parvovirus B19 NS1 Protein in Chronic and Inflammatory Diseases. (6th June 2022) - Jalali, Sedigheh; Farhadi, Ali; Rafiei Dehbidi, Gholamreza; Farjadian, Shirin; Sharifzadeh, Sedigheh; Ranjbaran, Reza; Seyyedi, Noorossadat; Namdari, Sepide; Behzad-Behbahani, Abbas
Abstract : Background . The nonstructural protein (NS1) of human parvovirus B19 (hPVB19) is considered to be a double-edged sword in its pathogenesis. NS1 protein promotes cell death by apoptosis in erythroid-lineage cells and is also implicated in triggering and the progression of various inflammation and autoimmune disorders. Objectives . We investigated the possible role of hPVB19 NS1 in the modulation of proinflammatory cytokines in nonpermissive HEK-293T cells. Methods . A plasmid containing the fully sequenced NS1 gene (pCMV6-AC-GFP-NS1) was transfected into HEK-293T cells. Transfection efficiency was assessed by fluorescent microscopy over time. Mock (pCMV6-AC-GFP) transfected cells were used as controls. The percentage of apoptotic cells was measured by flow cytometry at 24, 48, and 72 h posttransfection. Interleukin 6 (IL-6) mRNA, as a pleiotropic cytokine, was measured by real-time PCR. Furthermore, cellular supernatants were collected to determine the type and quantity of cytokines produced by mock- and NS1-transfected cells using flow cytometry. Results . Fold change in the expression level of IL-6 mRNA in transfected cells after 72 hr of incubation was found to be 3.01 when compared with mock-transfected cells; however, cell apoptosis did not happen over time. Also, the concentration of cytokines such as IL-2, IL-6, IL-9, IL-17A, IL-21, IL-22, interferon (IFN)- γ, and tumor necrosis factor α (TNF- α ) increased in NS1-transfected cells. Conclusions . Overall, our results indicated that proinflammatory cytokine levels had increased following the expression of hPVB19 NS1 in HEK-293T cells, consistent with a role for NS1 expression facilitating the upregulation of inflammatory reactions. Therefore, hPVB19 NS1 function may play a role in the progression of some chronic and inflammatory diseases.